A driver-heterogeneous car-following model - Muñoz-Figueroa, José; Cortés, Cristián E.; Martínez, Francisco (Congreso Chileno de Ingeniería de Transporte, 2013)
We extend and merge Mahut’s and Newell’s car-following models to include heterogeneous desired speeds of vehicles, which becomes relevant for proper mimicking of platoon formation and evolution. The proposed model offers a complete description of traffic dynamics over a given highway stretch, where delays occur at the end. Illustrative numerical examples are conducted with several model specifications, showing scattering of the fundamental diagrams, the “capacitydrop” phenomena, and stop-and-go waves related to “phantom jams”; therefore it shows traffic hysteresis as well.